Influence of rainfall on bunches production of oil palm accessions in the Brazilian Central Amazon (Research, Society and Development, 2024)
The palm oil production chain is affected by problems such as decline productivity, sazonality (period of the year) and alternation (variation between years) production, which are associated with climatic factors and plants genotype. Among climatic conditions, rainfall is the factor with the greatest influence on the productivity variations. The objective of the study was to evaluate the influence of rainfall on the bunches production of 34 oil palm accessions. The experiment was conducted at the Campo Experimental do Rio Urubu - Embrapa Western Amazon, municipality of Rio Preto da Eva, Amazonas. The evaluation of bunches production was carried out from the 5th to the 11th year after planting and rainfall data recorded between 2002 and 2011. The production components evaluated were number of bunches (NC), average bunch weight (PMC) and productivity of fresh fruit bunches (CFF). As the plants grew older, there was a reduction in NC and an increase in PMC. The rainfall had a significant influence on the all bunch production components. In years with regular rainfall, according to the region's history, the PMC in the 2nd half of the year is higher than in the 1st. The variation in the volume of precipitation influences the production components but does not change the harvest period. In the pedoclimatic conditions of the Central Amazon, the accessions of Tanzanian origin present a different distribution of annual bunches production than the accessions of the other origins studied.